The effect of leaf powder ofCucurbitamaxima Duck in management of onion Alliumcepa L. weeds (Damascus University Journal of agriculture sciences, 2022)
The current study Study the study of the allelopathic effect of Cucurbita maxima leaf powder on the herbs associated with the onion crop Allium cepa in germination and some agricultural crops in the fields of biocontrol studies and studies at the Faculty of Agricultural Engineering Damascus (Syria) during the year 2020. Significant reduction in the number of seaweed plants The negative (only water) was 23.3. Whereas the treatment of trifluralin (the positive control) to the effect was significant for the numbers of herbaceous plants (3.31), followed by the treatment of 200 g / line, where the number of herbals was reduced to 8.32 and corresponded to the treatment of 150 g / line (10.65), and the treatment of 100 g / line was the least effective. (14.15) plant / line. I have contributed to all treatments to reduce the percentage of dry matter of herbs in different treatments and the best treatments were the treatment of the herbicide at the recommended concentration (5 days before planting) 19.02 g / line and these results were consistent with a treatment of 200 g powder / line with half the pesticide concentration (before planting B 5 days) 20.57 g / line, followed by the rest of the transactions. The treatment of 100 g powder / line with a quarter of the pesticide concentration (5 days before planting) did not achieve significant differences with the negative control, and this indicates the importance of using pumpkin powder to reduce the amount of pesticide used. It was also found that the pesticide treatment (the recommended concentration of trifloralen 5 days before planting) resulted in achieving the highest dry matter percentage for onion plants 57.14g, followed by the 200g / line treatment with half the recommended concentration of the herbicide (5 days before planting) which It achieved 43.55 g, then 150 g / line treatment with half the recommended concentration of the herbicide (5 days before planting) and then in the rest of the treatments and the lowest percentage was in the negative control treatment, meaning that any addition of squash leaf powder with or without the pesticide may It achieved acceptable efficacy on increasing weights in crop plants.
Keywords: Allelopathic effect; leaf powder; Big pumpkin; Cucurbita maxima Duck; Weeds